Aplication Of Sensorimotor Playing To Increase Cognitive and Fine Motor Children - Septi Damai Yanti; Turdjai Turdjai (DIADIK, 2017)
The objective of the study to describe the application method sensorimotor playing to increase cognitive and fine motor children in group A1 PAUD Negeri Pembina 1 Bengkulu city. The type of research used is classroom action research. Subject of research on PTK is 15 children group A1 PAUD Negeri Pembina 1 Bengkulu City. Technique data used is observation. Data analysis technique used scores, averages, and t-test. Based on research results can be concluded that application of sensorimotor playing method can improve the children cognitive and fine motor from undeveloped (BB) be developed very well (BSB). There results show that sensorimotor play method effectively improving the cognitive and fine motor of the children in the group A1 PAUD Negeri Pembina 1 Bengkulu City.Key words: method sensorimotor playing, cognitive, fine motor